Penggalian Nilai-Nilai Pancasila Berbasis Kearifan Lokal Bali Dalam Rangka Penguatan Wawasan Kebangsaan - I Nyoman Wiratmaja; I Wayan Gede Suacana; I Wayan Sudana (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Warmadewa, Denpasar-Bali, Indonesia, 2021)
Consensus on Pancasila is not only because all parties are deeply aware of the need to build a National Insight and Indonesian Unity, but also because Pancasila contains elements that are upheld by all groups and levels of Indonesian society. Pancasila from its reality dimension implies that the basic values of ideology come from the real values of living in a very plural society, including the values of local wisdom that grow in the life of Balinese people. Bali, as one of the pillars of the integrity of the Nation and State, really needs and must be able to always contribute positively and significantly in the effort to achieve common goals. For this reason, this paper focuses on problems related to efforts to explore the values of Balinese local wisdom which are in line with the values of Pancasila in order to strengthen national insight. Balinese people in their daily life practices have local wisdom that cannot be separated from the teachings of Hinduism, which always maintain the balance of Skala and Niskala. Panca Sradha, Tri Kona, Tri Hita Karana, Tri Kaya Parisudha, Catur Purusa Artha, Vasudhaiva Kutumbakam, Loka Samasta Sukhina Bhavantu, Bhinneka Tunggal Ika, Tat Twam Asi, Yadnya, Ngayah, Sangkep, and other local wisdom values are the value of local wisdom which is very much in line with Pancasila.